2018
DOI: 10.1057/s41287-018-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Technology Adoption and Collective Action Important in Accessing Credit? Evidence from Milk Producers in Tanzania

Abstract: One of the targets of Sustainable Development Goal 2 is to double agricultural productivity and incomes of small-scale food producers through, among other things, improving access to financial services including credit. However, designing appropriate mechanisms for increasing access to credit by poor households remains a challenge, especially in Sub-Saharan Africa. This paper argues that technology adoption and collective action could provide pathways to enhancing access to credit. Evidence from milk-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…Dairy agripreneurs are, therefore, incentivised to sell to a market choice that cares for their production needs, which in this case were the cooperative market channels. This finding is similar to that of Twine et al (2018), who found that dairy agripreneurs opted to sell milk to cooperative due to availability of animal health services such as deworming and vaccination services. Therefore, access to deworming support service increases the likelihood of dairy agripreneurs selling milk to dairy cooperatives.…”
Section: Resultssupporting
confidence: 86%
“…Dairy agripreneurs are, therefore, incentivised to sell to a market choice that cares for their production needs, which in this case were the cooperative market channels. This finding is similar to that of Twine et al (2018), who found that dairy agripreneurs opted to sell milk to cooperative due to availability of animal health services such as deworming and vaccination services. Therefore, access to deworming support service increases the likelihood of dairy agripreneurs selling milk to dairy cooperatives.…”
Section: Resultssupporting
confidence: 86%
“…Farmer membership in the group was used as an important aspect of access to geoisolator technology information. The important of farmer group membership in affecting adoption positively is also in agreement with several other studies, for example, Uaiene et al (2009) in Mozambique, Asmelash (2014) in Ethiopia, Aryal et al (2018) in India, (Twine et al (2018) in Tanzania and Murage et al (2019) in Kenya who reported that farmer in an agricultural organization will help a farmer to have access to credit, extension, and market.…”
Section: Factors Affecting the Decision Of Salt Farmer To Adopt Geoissupporting
confidence: 87%
“…The effect on efficiency is confirmed in Table 2, which reveals that milk producers that are a member of a group or organization are technically more efficient than those who are not. This finding is in line with Twine et al (2019), which shows group membership increases the probability of borrowing and the number of funds borrowed by milk-producing households in Tanzania. The group membership variable is highly correlated with the commercialization index dummy variable; hence it was dropped in model 2.…”
Section: Determinants Of Technical Efficiencysupporting
confidence: 87%